Analysis of Carbon Contents and Heavy Metals in Coal Samples Using Calibration-free LIBS Technique - Muhammad Aamir Israr; Qamar Abbas; Sami Ul Haq; Ali Nadeem (Journal of Spectroscopy)
We report a compositional analysis of four coal samples collected from different mines in Pakistan and one Chinese brand. The coal samples were pelletized in the form of a disc and irradiated with a focused laser beam of fundamental (1064 nm) and second (532 nm) harmonics of Nd:YAG laser, which produced plasma on the sample surface. The plasma emissions were recorded using a broadband (200–800 nm), high-resolution spectrometer (LIBS2500plus, Ocean Optics Inc., USA), which shows that the emission spectra from 532 nm, were more intense and dense in comparison with 1064 nm spectra. The compositional analysis of coal samples was performed using the calibration-free LIBS technique, utilizing the plasma temperature and self-absorption corrected emission line intensities. The analysis yields a number of major and trace elements in coal samples, among which the concentration of carbon varies from 642 to 718 g/kg, and sulfur contents were detected as 1.1 to 7.2 g/kg. The heavy metals chromium and lead were detected in the range of 14 to153 and 210 to 252 ppm, respectively. In addition, the gross calorific value (GCV) of all the coal samples was estimated using the concentrations of carbon, hydrogen, nitrogen, oxygen, and sulfur from 26.40 to 27.18 MJ/kg, which is an important parameter to determine the coal quality and burning efficiency.